Analisis Pendidikan Karakter Berbasis Kearifan Budaya dan Lingkungan sebagai Upaya Mewujudkan Profil Pelajar Pancasila di Sekolah Dasar - Elisya Risma Salsabilla; Zalfa Nabila Aprillianti; Nissa Nafida Alma; Aurel Zahwa Mutiara Dealova; Via Widyawati; Delia Indrawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of character education that focuses on cultural and environmental wisdom in encouraging the creation of the Pancasila Student Profile at the elementary school level. This study employed a systematic literature review method with inclusion criteria consisting of articles relevant to character education, local wisdom, and environmental education at the elementary school level published between 2015 and 2025, with a total of 12 articles analyzed using thematic analysis. The results indicate that local cultural wisdom contributes significantly to instilling values such as cooperation, tolerance, and responsibility, while environmental education builds students' ecological awareness. Several studies demonstrate that local wisdom contributes significantly to character formation, though differences exist in implementation approaches Hidayah et al. (2019) emphasize the integration of values in learning, while Devina et al. (2023) focus more on habituation in daily activities. The integration of both approaches makes learning more contextual and meaningful, thus supporting holistic character formation. However, its implementation still faces obstacles such as a lack of program consistency and teacher readiness in integrating character values. This research contributes to integrating two approaches cultural wisdom and environmental education within the framework of character education in elementary schools